2014
DOI: 10.1016/j.jtcvs.2013.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparing robot-assisted thoracic surgical lobectomy with conventional video-assisted thoracic surgical lobectomy and wedge resection: Results from a multihospital database (Premier)

Abstract: RATS lobectomy and wedge resection seem to have higher hospital costs and longer operating times, without any differences in adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 13 publications
12
166
3
7
Order By: Relevance
“…Premier's methodology and database, in which individualized severity-adjusted expected outcome parameters are calculated for each patient, are regularly used to evaluate mortality, costs, complications, morbidity, and resource utilization across a wide variety of patients and disease states [21,[24][25][26][27][28]. In this study, we focused on illnesses related to poisoning or toxic effects of drugs and demonstrated that inpatients primarily cared for by medical toxicologists, compared to patients primarily cared for by non-toxicologists and adjusted for predicted values, experienced significantly shorter hospital stays, generated lower costs, and suffered lower mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premier's methodology and database, in which individualized severity-adjusted expected outcome parameters are calculated for each patient, are regularly used to evaluate mortality, costs, complications, morbidity, and resource utilization across a wide variety of patients and disease states [21,[24][25][26][27][28]. In this study, we focused on illnesses related to poisoning or toxic effects of drugs and demonstrated that inpatients primarily cared for by medical toxicologists, compared to patients primarily cared for by non-toxicologists and adjusted for predicted values, experienced significantly shorter hospital stays, generated lower costs, and suffered lower mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012 (at the time of data acquisition), Premier's database contained information extracted from 860 US hospitals who contract with Premier for quality measures database management. The Premier database accounted for more than 25 % of all inpatient discharges, nationally, at the time of this study [20,21]. This database contained risk-adjusted outcomes for length of stay (LOS; days), cost (dollars, standardized with cost-to-charge ratio), and mortality (percent), wherein each patient discharge was severity-adjusted independently and given its own expected outcome that was matched to the observed outcome.…”
Section: Methodsmentioning
confidence: 99%
“…In many countries in which medical services are covered by health insurance, the increase in medical costs induced by robot surgery aims at the ultimate decrease in medical costs by shortening the length of hospitalization and reducing postoperative complications. It seems that decisions on the medical system of robotic surgery in the future require comprehensive investigations incorporating an overall view and comprehension of the medical system as a single integrated whole concept, [1][2][3][4][5][6] and it is essential for future stable development that the problem should be settled as soon as possible. It seems that the economic management in the unit institution is enabled if the dVS would be utilized in combination with urology, gynecology, and gastrointestinal surgery under the present Japanese conditions, that is, as shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, robot-assisted partial nephrectomy (RAPN) for small renal cell carcinomas (cT1N0M0) has also become eligible for reimbursement by the JNHIS since April 2016. According to several investigations of cost-effectiveness in countries outside Japan, robot-assisted thoracic surgery (RATS) has a financial deficit from the point of view of health economics in comparison with VATS, [1][2][3][4][5][6] despite differences in the medical health insurance systems. Other clinical fields are still waiting for reimbursement for the da Vinci Surgical System (dVS) operations, for example, gastrectomy, uterectomy, and thymectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, RATS may become a better option than VATS for trachea surgery. However, there are still some disadvantages of RATS, including higher hospital costs, loss of haptic feedback, longer set-up times, and concern regarding the management of accidental intraoperative bleeding (24,25). Additionally, there are only limited number of reports on the utilization of RATS for airway surgery compared to VATS and conventional thoracotomy surgery.…”
Section: Potential Role Of Robot Assisted Thoracic Surgery (Rats) Formentioning
confidence: 99%